Rotator Cuff Repair With Bone Grafting of Greater Tuberosity Cyst: A Technique Video - Brian Forsythe MD; Vahram Gamsarian BE; Caitlin Ward MD; Vikranth Mirle BS; Christopher M. Brusalis MD (Video Journal of Sports Medicine, 2023)
Background: Nearly 500,000 rotator cuff repairs are performed annually in the United States. Cysts within the humeral head have been reported to occur in more than half of patients diagnosed with a rotator cuff tear. They are related to age-related degeneration and rotator cuff dysfunction, and may arise from congenital abnormalities. Indications: Humeral head cysts may pose technical challenges during rotator cuff repair. Cysts located at the footprint of a planned rotator cuff repair can decrease biological healing capacity and reduce the fixation strength of suture anchors. One treatment strategy to address bone loss secondary to humeral head cysts is to incorporate cancellous allograft bone chips, which provide an osteoconductive scaffold for bone formation. Technique Description: Standard arthroscopic portals were established and during arthroscopy, the rotator cuff tear was identified, and tissue was mobilized. The cyst was debrided to healthy, bleeding bone using curettes and an arthroscopic shaver. A 2.5 mL sterile syringe was packed with crushed, cancellous allograft bone chips. The tip of the syringe was removed to allow for a wider aperture to facilitate injection of bone chips. Through an accessory, percutaneous portal just lateral to the acromion, the syringe was inserted into the cyst site, and bone graft contents were injected into the cyst. Pressure was applied to the syringe to impact the bone graft material. The bone chips were impacted with the syringe plunger. Following rotator cuff repair, the patient underwent subacromial decompression, distal clavicle excision, and open sub-pectoral biceps tenodesis with suture anchor fixation. Discussion/Conclusion: Greater tuberosity cysts can impose a technical challenge during arthroscopic rotator cuff repair. Incorporation of impacted cancellous allograft bone chips is an efficient, reproducible method to enhance healing of the RTC tendon enthesis. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.